?THE FOOD AND FEEDING HABITS OF FISHES OF THE JAMIESON RIVER, NIGERIA (Biological Sciences - PJSIR, 2003)
121 specimens of teleosts comprising of 23 species, 17 genera and 11 families were examined in the study of the ichthyo- faunal food habits of the Jamieson River. Cichlidae (34.78%) was richest in species number, and a Bagridae, Chrysichthys furcatus (28.93%) was the most numerical species. Analysis of the stomach contents revealed algae, diatoms, macro- phytes, zooplankton, shrimps, insects, fish, fish scales, detritus, sand and unidentified material as the main food catego- ries selectively eaten by Jamieson River fishes. The fishes exhibited benthopelagic exploitation and grazing tendency.